Evaluation of [68Ga]Ga-NODAGA-RGD for PET Imaging of Rat Autoimmune Myocarditis - Jahandideh, Arghavan; Ståhle, Mia; Virta, Jenni; Li, Xiang-Guo; Liljenbäck, Heidi; Moisio, Olli; Knuuti, Juhani; Roivainen, Anne; Saraste, Antti (Frontiers in Medicine, 2021)
[68Ga]Ga-NODAGA-RGD is a positron emission tomography (PET) tracer binding to cell surface receptor αvβ3 integrin that is upregulated during angiogenesis and inflammation. We studied whether αvβ3 targeting PET imaging can detect myocardial inflammation in a rat model of autoimmune myocarditis. To induce myocarditis, rats (n = 8) were immunized with porcine cardiac myosin in complete Freund’s adjuvant on day 0 and 7. Control rats (n = 8) received Freund’s adjuvant alone. On day 21, in vivo PET/computed tomography (CT) imaging with [68Ga]Ga-NODAGA-RGD followed by ex vivo autoradiography and immunohistochemistry were carried out. Inflammatory lesions were detected histologically in the myocardium of 7 out of 8 immunized rats. In vivo PET images showed higher [68Ga]Ga-NODAGA-RGD accumulation in the myocardium of rats with inflammation than the non-inflamed myocardium of control rats (SUVmean 0.4 ± 0.1 vs. 0.1 ± 0.02; P = 0.00006). Ex vivo autoradiography and histology confirmed that [68Ga]Ga-NODAGA-RGD uptake co-localized with inflammatory lesions containing αvβ3 integrin-positive capillary-like structures. An ex vivo autoradiography with non-specific [68Ga]Ga-DOTA-(RGE)2 tracer showed 76% lower uptake in the inflamed myocardium. Our results indicate that αvβ3 integrin-targeting [68Ga]Ga-NODAGA-RGD is a potential PET tracer for the specific detection of active inflammatory lesions in autoimmune myocarditis.